How Students of the Eighth Grade of Elementary School and the First Grade of High School Interpret the Representations of the Structure and Composition of Substances - Dragica D. Trivić; Lidija R. Ralević; Biljana I. Tomašević (University of Belgrade, Teacher Education Faculty, 2021)
The aim of this research is to examine how students in the eighth grade of elementary school and the first grade of high school interpret the representations of the structure and composition of substances and how successful they are in transforming the representations of one level into another. A total of 193 students participated in the research, 81 students of the eighth grade of elementary school and 112 students of the first grade of high school. According to the aim of the research and research questions, a test was prepared whose requirements referred to different levels of representations related to the structure of atoms, molecules and ions, chemical bonds, pure substances and mixtures. The students in the first grade of high school achieved a statistically significantly better overall achievement on the test compared to the students in the eighth grade of elementary school. The results of the research show that submicroscopic level representations help the eighth-grade students less in understanding the structure of atoms, molecules and ions, as well as the composition of pure substances and mixtures, while the first-grade high school students are more successful in their interpretation. In addition, the research results have shown that there are problems in translating the meaning of one level of representations to another, especially when information is conveyed using submicroscopic-level representations.